2022
DOI: 10.1093/bjs/znac007
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological mechanisms of ALPPS: experimental model

Abstract: Background Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) is a two-stage strategy that may increase hepatic tumour resectability and reduce postoperative liver failure rate by inducing rapid hypertrophy of the future liver remnant (FLR). Pathophysiological mechanisms after the first stage of ALPPS are poorly understood. Methods An ALPPS model was established in rabbits with liver VX2 tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Although some FIGURE 4 CT images after stage one showing partitioned liver and surgical clips along the transection line. authors recommend prolonging the interval between the two stages to 3-4 weeks, most support the thesis that a prolonged waiting period may increase the risk of tumor growth and metastasizing (3,8,24,25). Second volumetry showed a significant TLV increase in both groups.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Although some FIGURE 4 CT images after stage one showing partitioned liver and surgical clips along the transection line. authors recommend prolonging the interval between the two stages to 3-4 weeks, most support the thesis that a prolonged waiting period may increase the risk of tumor growth and metastasizing (3,8,24,25). Second volumetry showed a significant TLV increase in both groups.…”
Section: Discussionmentioning
confidence: 71%
“…Previous research has shown significant variability in FLR hypertrophy following ALPPS, prompting investigations into various technical aspects and disease factors influencing outcomes. Therefore, many authors studied technical ALPPS characteristics, liver parenchymal condition, and patient comorbidities as potential factors of FLR hypertrophy ( 2 , 3 , 8 , 13 16 ). However, the impact of the liver transection line on FLR hypertrophy has not been thoroughly explored, and understanding the dynamics of FLR hypertrophy is critical for optimizing surgical outcomes and minimizing complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations